STRATEGI KOMUNIKASI KONTROL JEJARING KEBIJAKAN DALAM GERAKAN BERSAMA RAKYAT ATASI KAWASAN PADAT KUMUH DAN MISKIN (GEBRAK PAKUMIS) DI KABUPATEN TANGERANG - Ilhami, Rizky; Affandi, Nur Ratih; Hartawan, Yusuf (Ilmu Komunikasi, FISIP Universitas Pasundan, 2021)
Housing and settlements have a very fundamental role in the life of the Indonesian people considering the problem that often occurs is the level of housing needs that is not balanced with the level of regional capacity in providing habitable housing. As a result, a residential area will receive a load that exceeds the carrying capacity of its environment and tends to become slum. The problem of settlements is a serious problem because it is feared that it will cause fatal pockets of poverty and then cause various social problems beyond the government's ability to handle and monitor them. The Tangerang Regency government tries to clean up uninhabitable houses through the GEBRAK PAKUMIS Program. The main focus of this program is to improve the water and sanitation sector with a focal point on improving the quality of houses because a poor sanitation system is a major factor in the formation of slum areas. This study aims to analyze and find theoretical answers to the principles of policy networks and obtain new concepts about policy networks. This research uses descriptive qualitative methods, data collection techniques by means of interviews, observation, and documentation. One of the problems that is the basis for the failure of this program is the long procedure. This is something that is feared by residents, because it is considered difficult to be realized. Based on the problems faced by residents as recipients of house renovation assistance, environmental development and community empowerment, the correct communication strategy is a solution to communicate the benefits of the program to the beneficiary residents. Therefore, the communication strategy solution offered in this study is as a stimulant for local government to provide populist socialization to residents in order to bring citizens to ease in taking procedures in this program.